Evaluation of impression difference of a domestic mobile manipulator with autonomous and/or remote control in fetch-and-carry tasks. (17th October 2020) - Yamamoto, Takashi; Yaguchi, Hiroaki; Kato, Shohei; Okada, Hiroyuki
Abstract : Various studies on autonomous robots that perform physical tasks in living environments are being conducted at present to solve the social problems of an aging society with a low birth rate. However, because it remains difficult for all robots to work autonomously in complicated environments, remote control robots may be useful for practical applications. As the purpose of remote control robots is to make direct connections between the operator and user, they may reduce affinity between the robot and the user. In this study, we define autonomous remote control robots with the aspects of both autonomy and remote operation explicitly. Affinity is compared among autonomous remote control robots, remote control robots, and autonomous robots, through controlled experiments on interactions in fetch-and-carry tasks using a domestic mobile manipulator, Human Support Robot, on a test field that is compliant with the World Robot Summit 2020 Rulebook. The results demonstrate that affinity exhibits the following order: autonomous robots, autonomous remote control robots, and remote control robots. Considering that autonomous robots remain under development, autonomous remote control robots may be beneficial for expanding the abilities of physical tasks and social acceptance. GRAPHICAL ABSTRACT: UF0001